SISTEM KENDALI PROPORSIONAL, INTEGRAL, DAN DERIVATIF (PID) PADA PERSAMAAN PANAS - Muhammad Ikhwan; Said Munzir; Nurmaulidar Nurmaulidar (Jurnal Natural, 2016)
This research showed the application of Proportional, Integral, and Derivative (PID) control system on heat equations that has non-integer ordered solutions on Laplace domain. Zala tuning method and Ziegler-Nichols method; which is ultimate cycle and process reaction method, are used to determine the value of Kp, Ti and Td as constants in PID to maintain the temperature of 1oC on the position of x = 3 m from the heat source with k = 0,042 m2s-1 diffusivity. Based on the results, there were ten systems that were closest in the desired criteria. With regards to overshoot and the time taken to reach the stable position, therefore the ten systems that are produced have not many differences in strengths and weaknesses.